2019
DOI: 10.1186/s13072-019-0317-2
|View full text |Cite
|
Sign up to set email alerts
|

The distributions of protein coding genes within chromatin domains in relation to human disease

Abstract: BackgroundOur understanding of the nuclear chromatin structure has increased hugely during the last years mainly as a consequence of the advances in chromatin conformation capture methods like Hi-C. The unprecedented resolution of genome-wide interaction maps shows functional consequences that extend the initial thought of an efficient DNA packaging mechanism: gene regulation, DNA repair, chromosomal translocations and evolutionary rearrangements seem to be only the peak of the iceberg. One key concept emergin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This suggests that genes in TADs on their own are less tolerant to mutation and therefore more functionally important. This is supported by Muro et al [ 39 ] who recently found that genes which singly occupy a TAD are more likely to be associated with disease. We analysed the functional enrichment of the genes singly occupying TADs and found a strong enrichment for developmental processes.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…This suggests that genes in TADs on their own are less tolerant to mutation and therefore more functionally important. This is supported by Muro et al [ 39 ] who recently found that genes which singly occupy a TAD are more likely to be associated with disease. We analysed the functional enrichment of the genes singly occupying TADs and found a strong enrichment for developmental processes.…”
Section: Discussionmentioning
confidence: 58%
“…Using bedtools intersect [ 47 ], protein-coding genes were overlapped and assigned to a TAD if their start and end position fell within the same TAD. This TAD-gene mapping method is more stringent than previously used [ 17 , 18 , 39 ], but it allows us to focus on genes which can be confidently assigned to a TAD and controls for the possibility that genes which overlap a TAD boundary may have different features. This is especially important given recent evidence has shown that TAD boundaries are often not “sharp”, instead boundaries can span “zones of transition” meaning that it may not be possible to confidently assign genes spanning a TAD boundary to one TAD or the other [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that genes in TADs on their own are less tolerant to mutation and therefore more functionally important. This is supported by Muro et al (33) who recently found that genes which singly occupy a TAD are more likely to be associated with disease. When we separated TADs into CTCF TADs and non-CTCF TADs we found that this relationship is stronger for CTCF TADs compared to non-CTCF TADs (Supplementary figure 6).…”
Section: Discussionmentioning
confidence: 60%
“…Using bedtools intersect (40), protein coding genes were overlapped and assigned to a TAD if their start and end position fell within the same TAD. This TAD-gene mapping method is more stringent than previously used (16,17,33) but it allows us to focus on genes which can be confidently assigned to a TAD and controls for the possibility that genes which overlap a TAD boundary may have different features. This is especially important given recent evidence has shown that TAD boundaries are often not "sharp", instead boundaries can span "zones of transition" meaning that it may not be possible to confidently assign genes spanning a TAD boundary to one TAD or the other (41) In order to assess the functional similarity between pairs of genes in TADs, unless otherwise stated olfactory genes were removed from analysis.…”
Section: Overlapping Tads With Protein Coding Genesmentioning
confidence: 99%
“…Disruption of TADs during development is implicated in ectopic gene expression and disease ( Ibn-Salem et al, 2014 ; Lupianez et al, 2015 , 2016 ; Muro et al, 2019 ). Comparison of genome architecture in primate, mouse, cattle, opossum, chicken, clawed frog, and zebrafish showed conservation of non-coding regions that coincide with TAD boundaries ( Harmston et al, 2017 ; Krefting et al, 2018 ).…”
Section: Mechanisms Of Epigenetic Regulation Of Gene Expressionmentioning
confidence: 99%